Ship-based MAX-DOAS measurements of tropospheric NO2 and SO2 in the South China and Sulu Sea. (February 2015) - Schreier, S.F.; Peters, E.; Richter, A.; Lampel, J.; Wittrock, F.; Burrows, J.P.
Abstract: In November 2011, ship-based Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) measurements were performed within the SHIVA campaign on board RV Sonne in the South China and Sulu Sea. Spectral measurements for a total of eleven days could be used to retrieve tropospheric slant column densities (SCDs) of nitrogen dioxide (NO2 ) and sulfur dioxide (SO2 ) in the marine environment. The NO2 fit was performed following recommendations developed during the CINDI campaign and adapted for the ship-based measurements. We found that the inclusion of a cross section for liquid water and an empirical correction spectrum accounting for the effects of liquid water and vibrational Raman scattering (VRS) slightly improved the NO2 fit quality, especially at lower elevation angles and for lower NO2 levels. The conversion of SCDs into tropospheric NO2 vertical columns (TVC NO2 ) has been achieved using both a simple geometric approach and the Bremian advanced MAX-DOAS Retrieval Algorithm (BREAM), which is based on the optimal estimation method and accounts for atmospheric radiative transfer. We found good agreement between the geometric approach using the 15° measurements and BREAM, revealing that measurements at 15° elevation angle can be used for retrieving TVC NO2 in tropical marine environments when SZA is smaller than 75°. As expected, the values of TVC NO2 were generally low (<0.5 × 10 15 molec cm −2 ) when no sources of NO x were in proximity to the RV Sonne. However, we found increased values of TVC NO2 (>2 × 10 15 molec cm −2 ) in the morning when the RV Sonne was heading along the coast of Borneo. This is in good agreement with satellite measurements. The results of the profile retrieval show that the boundary layer values of NO2 are <30 pptv in the open and clean tropical marine environment. Interestingly, we also found elevated tropospheric SO2 amounts for measurements taken in a busy shipping lane, consistent with the time series of tropospheric NO2 . Highlights: A profile retrieval approach to derive tropospheric NO2 vertical columns is applied. The simple geometric approximation using 15° measurements can also be used. Time series of NO2 and SO2 are in good agreement in a busy shipping lane.